Ozone detoxification of patulin in aqueous solution and cytotoxic evaluation using human hepatic carcinoma cells. (1st December 2018) - Diao, Enjie; Ren, Dongliang; Liu, Tingwu; Zhang, Jianmei; Hu, Weicheng; Hou, Hanxue
Abstract: Patulin often contaminates fruits and fruit-base products, which seriously threats the health of consumers. In this study, ozone was used to degrade patulin in aqueous solution, and investigated the cytotoxicity of patulin after ozone detoxification on human hepatic carcinoma cells (HepG2) using MTT assay and apoptosis assay. Patulin was rapidly degraded from 24.59 mg/L to 9.85 mg/L within 180 s by 10.60 mg/L of ozone at a flow rate of 90 mL/min, and reduced by 59.94%. The half maximal inhibitory concentration (IC50 ) of patulin on HepG2 cells was 9.32 μmol/L after 24 h of exposure, and it showed a dose dependent effect. After 90 s of ozone detoxification, the cell viability of HepG2 cells obviously increased from 42.31% to 93.96%, and the total apoptotic cells significantly reduced from 22.24% to 11.18% after 180 s of ozone treatment. The results clearly show the great potential of ozone in degrading patulin in liquid foods. Graphical abstract: Highlights: Ozone can rapidly degrade patulin in aqueous solution. Cytotoxic effects induced by patulin were investigated. IC50 of patulin on HepG2 cells was determined. Ozone can significantly reduce the cytotoxicity of patulin on HepG2 cells.